Accountability in Government Contracting Arrangements: Experimental Analysis of Blame Attribution Across Levels of Government. Issue 4 (May 2021) - Leland, Suzanne; Mohr, Zachary; Piatak, Jaclyn
While governments increasingly turn to third-party providers to deliver public services and government responsibilities are increasingly shifted from the federal to the state and local levels, both contracting and the division of powers under federalism blur lines of accountability. Because recent experiments on blame shifting find mixed results and citizens have different expectations of federal, state, and local government, we ask the following: How does blame attribution in third-party governance compare across levels of government? To address this question, we employ a timely survey experiment to examine who is responsible for a prisoner's death in the case of interstate prisoner transport, which is one of the few services that is provided across all levels of government and by government contractors. The results show that contracting reduces the level of blame attributed to the government and that blame for contract failures varies by the level of government. Across levels of government, we find the local government sees the largest reduction in blame by contracting out. Findings have implications for accountability in contracting arrangements in public safety contexts.